1992
DOI: 10.2134/agronj1992.00021962008400050013x
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa Yield Component Responses to Seeding Rate Several Years after Establishment

Abstract: Little information is available regarding the relationships of alfalfa (Medicago sativa L.) forage yield with yield components in seed‐established stands grown under dryland conditions. Field experiments that included two cultivars and 15 seeding rates ranging from m 2.2 to 33.6 kg pure live seed ha−1 were established in 1985 at Brookings and Highmore, SD. The objective was to determine seeding rate effects on components of alfalfa forage yield and on plant morphology several years after establishment. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
29
1
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 0 publications
10
29
1
2
Order By: Relevance
“…The conclusion that higher plant densities resulted in higher lucerne biomass and total biomass in most years supports the findings of Volenec et al (1987), Kephart et al (1992) and Dear et al (2007b). However, this is probably because plant densities in all of these studies, especially in our study, were relatively low (Hall et al 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The conclusion that higher plant densities resulted in higher lucerne biomass and total biomass in most years supports the findings of Volenec et al (1987), Kephart et al (1992) and Dear et al (2007b). However, this is probably because plant densities in all of these studies, especially in our study, were relatively low (Hall et al 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Farming systems which have included lucerne in the rotation in this region usually consist of lucerne based pastures for 3-4 years followed by crop (Latta et al 2001) so the benefits of a higher plant density were reduced by possibly one year. Previous research has generally found that plants in higher density populations experienced higher mortality rates than lower-density populations (Kephart et al 1992;Hall 1993;Nelson et al 2001;Dear et al 2007b). However, densities in these studies were higher than what we achieved at both Esperance and Katanning.…”
Section: Discussionmentioning
confidence: 95%
“…Porém, a mesma também se faz presente em trabalhos com plantas forrageiras, avaliando os componentes do rendimento de sementes (Iannucci & Martiniello, 1998;Lord & Kelly, 1999), bem como os componentes da produção de matéria seca (Gumber et al, 1988;Shukla & Malaviya, 1989;Kephart et al, 1992).…”
Section: Introductionunclassified
“…It reported that alfalfa plants were several inches shorter, lodge less, and more easily to pollinating insects in thinned stands than those in unthinned stands (Pederson, 1957). The recommended row spacing in these studies changed from 20 to 91 cm (Kephart et al, 1992). These studies indicate that low bush density and greater row spacing are important elements for increasing alfalfa seed production.…”
Section: Introductionmentioning
confidence: 93%